Combined effects of viscous dissipation and magnetohydrodynamic on periodic heat transfer along a cone embedded in porous Medium. (December 2022) - Ashraf, Muhammad; Ilyas, Asifa; Ullah, Zia; Ali, Aamir
The current analysis is focused on the periodic behaviour of convective heat transfer characteristics of fluid flow along the electrically conducting cone embedded in the porous medium with the inclusion of viscous dissipation effects in energy equation. The purposed nonlinear mathematical model is formulated by introducing periodic behaviour in conservations equations along with specific boundary conditions. The dimensioned equations are converted into dimensionless form by using suitable scaling variables. The physical properties such as velocity profile, temperature distribution and magnetic profile as well as periodic skin friction, rate of heat transfer and rate of current density are highlighted graphically for various dimensionless parameters involved in the purposed model. Furthermore, the physical impacts of emerging parameters with physical reasoning are illustrated periodically. The main contribution of this study is based on the solutions of non-oscillating part and then these solutions are used to analyse periodic behaviour of shear stress, rate of heat transfer and rate of current density in the presence of viscous dissipation.